PENGARUH ASIMETRI INFORMASI DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Amalia Indah Fitriana (Universitas Muhammadiyah Tangerang, 2017)
This study aims to analyze the influence of information asymmetry and firm size on earnings management.In this study the object of research is the Indonesia Stock Exchange. Indonesia Stock Exchange (IDX) or can also called Indonesia Stock Exchange (IDX). Form data in this research is quantitative data. The data used in this research is the company's financial report along with independent auditor's report on the consumer goods industry in IDX period 2011-2015. The sample is determined by purposive sampling. Data analysis methods used consist of descriptive statistical analysis, classical assumption test analysis, multiple linear regression analysis, coefficient of determination and correlation coefficient, and hypothesis test.Based on the results of research show the value of correlation coefficient (R) of 0.230. From the calculation results can be concluded the relationship between variables Asymmetry Information (X1), and Company Size (X2) to variable Management Profit (Y) is weak and positive. While the value of coefficient of determination (R2) seen from Adjusted R Square shows the value of 0.039 or 3.9%. Hypothesis test results show the sign value of 0,048 that information asymmetry significant effect on earnings management. The firm size variable shows a sign value of 0.98 that firm size has no significant effect on earnings management. While testing simultaneously shows sign value of 0.028 that information asymmetry and firm size together have significant effect to earnings management. Keywords: information asymmetry, firm size, earnings management